2005
DOI: 10.1002/anie.200500528
|View full text |Cite
|
Sign up to set email alerts
|

Coordinatively Unsaturated Cationic and Zwitterionic [Cp*Ru(κ2P,N)] Complexes: Ligand‐Assisted Double‐Geminal CH Bond Activation and Reversible α‐H Elimination at Ruthenium

Abstract: A masked variant of the first coordinatively unsaturated [Cp*Ru(κ2‐P,N)]+ cation (1) is reported, which has proven capable of single intramolecular CH activation. In contrast, the isostructural zwitterionic complex 2 apparently rearranges to a hydridocarbene by way of a remarkably facile, ligand‐assisted double CH bond activation process (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…20,21 Control experiments featured in these reports confirm the importance of tethered phosphino and primary/secondary amine moieties as a means of achieving optimal catalytic performance via Ru/NH bifunctional catalysis. 22,23 However, despite recent research efforts, 24,25 neither [Cp*Ru( 2 -PϳN)] + X − nor related neutral Cp*Ru( 2 -PϳN) species of the type invoked by Ikariya and coworkers featuring a tethered amido-phosphine ancillary ligand have proven isolable prior to our work reported herein.…”
Section: Introductionmentioning
confidence: 57%
“…20,21 Control experiments featured in these reports confirm the importance of tethered phosphino and primary/secondary amine moieties as a means of achieving optimal catalytic performance via Ru/NH bifunctional catalysis. 22,23 However, despite recent research efforts, 24,25 neither [Cp*Ru( 2 -PϳN)] + X − nor related neutral Cp*Ru( 2 -PϳN) species of the type invoked by Ikariya and coworkers featuring a tethered amido-phosphine ancillary ligand have proven isolable prior to our work reported herein.…”
Section: Introductionmentioning
confidence: 57%
“…Similarly, the replacement of the chloride in 160 by a non-coordinating B(C 6 F 5 ) 4 anion induces the activation of a NCH 2 -H bond and formation of complex 161 featuring a strained three-membered metallacycle (Scheme 68). 290 Reaction of complex 160 or 161 with a base affords the carbene metallacycle 162. ), 292 indicating that α-H elimination is fully reversible and that the cyclometalated product is not rigid.…”
Section: Rutheniummentioning
confidence: 99%
“…[103] Such structural patterns have also been observed in a range of other crystallographically characterized PGM zwitterions supported by P,N indenide and related ligands. [104][105][106][107][108][109][110][111][112] In the case of 67, it was also demonstrated that exclusion of either of the pnictogen donors affords more conventional h 5 -indenylrhodium species featuring a pendant donor fragment (71 and 72). Despite the apparently similar metal coordination spheres featured in these structurally related Group 9 cation/zwitterion pairs, catalytic studies examining (transfer) hydrogenation, [102,103,114] hydrosilylation, [101,103] and hydroboration [115] highlighted important reactivity differences within and between these classes of complexes.…”
Section: Carbanion-based Ancillary Ligationmentioning
confidence: 94%
“…[104,105] This reaction afforded the hydridocarbene 78, possibly via the unobserved target zwitterion 77 as an intermediate. The formation of 78 corresponds to net double geminal C À H bond activation of a NMe group in putative intermediate 77, with accompanying transfer of a proton to the indenide backbone.…”
Section: Carbanion-based Ancillary Ligationmentioning
confidence: 99%
See 1 more Smart Citation